2018
DOI: 10.1021/acs.orglett.8b02011
|View full text |Cite
|
Sign up to set email alerts
|

Stereodivergence in the Ireland–Claisen Rearrangement of α-Alkoxy Esters

Abstract: A systematic investigation into the Ireland-Claisen rearrangement of α-alkoxy esters is reported. In all cases, the use of KN(SiMe) in toluene gave rearrangement products corresponding to a Z-enolate intermediate with excellent diastereoselectivity, presumably because of chelation control. On the other hand, chelation-controlled enolate formation could be overcome for most substrates through the use of lithium diisopropylamide (LDA) in tetrahydrofuran (THF).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 20 publications
0
30
0
Order By: Relevance
“…In preparation for the bis(macrolacram) assembly, the individual amino acid synthons were obtained by Ireland‐Claisen rearrangement (ICR) of two esters prepared from allylic alcohol 4 (Scheme 3 a and b) [11] . Intermediate 2 was obtained from ester 15 (82 % yield, dr 10:1) under reaction conditions developed specifically for α‐alkoxy esters, where we found that the best chelation‐controlled outcome is achieved with KN(SiMe3)2/PhMe combination, while, surprisingly, LDA/THF affords non‐chelation controlled diastereomer with good selectivity, despite the expected higher propensity of lithium to coordinate with oxygen Lewis bases [12] . ICR of ester 16 gave rise to carboxylic acid 17 (87 % yield, dr 6:1), which, after forming the methyl ester with Me 3 SiCHN 2 , was advanced to amino ester 3 by azide reduction with SnCl 2 /PhSH (82 % yield) [13] …”
Section: Figurementioning
confidence: 88%
See 1 more Smart Citation
“…In preparation for the bis(macrolacram) assembly, the individual amino acid synthons were obtained by Ireland‐Claisen rearrangement (ICR) of two esters prepared from allylic alcohol 4 (Scheme 3 a and b) [11] . Intermediate 2 was obtained from ester 15 (82 % yield, dr 10:1) under reaction conditions developed specifically for α‐alkoxy esters, where we found that the best chelation‐controlled outcome is achieved with KN(SiMe3)2/PhMe combination, while, surprisingly, LDA/THF affords non‐chelation controlled diastereomer with good selectivity, despite the expected higher propensity of lithium to coordinate with oxygen Lewis bases [12] . ICR of ester 16 gave rise to carboxylic acid 17 (87 % yield, dr 6:1), which, after forming the methyl ester with Me 3 SiCHN 2 , was advanced to amino ester 3 by azide reduction with SnCl 2 /PhSH (82 % yield) [13] …”
Section: Figurementioning
confidence: 88%
“…[11] Intermediate 2 was obtained from ester 15 (82 % yield, dr 10:1) under reaction conditions developed specifically for a-alkoxy esters, where we found that the best chelation-controlled outcome is achieved with KN(SiMe3)2/PhMe combination, while, surprisingly, LDA/THF affords non-chelation controlled diastereomer with good selectivity, despite the expected higher propensity of lithium to coordinate with oxygen Lewis bases. [12] ICR of ester 16 gave rise to carboxylic acid 17 (87 % yield, dr 6:1), which, after forming the methyl ester with Me 3 SiCHN 2 , was advanced to amino ester 3 by azide reduction with SnCl 2 /PhSH (82 % yield). [13] Fragment union was achieved by amide formation from acid 2 and amine 3, followed by another azide reduction under the same conditions, ester hydrolysis, and macrolactamization.…”
mentioning
confidence: 99%
“…Each of these Grignard reagents are known. Their concentrations were titrated using Knochel’s method . Allylic alcohols were prepared according to the reported procedure . NMR spectra were recorded on a Bruker AV400 or Bruker AV300 spectrometer at 25 °C.…”
Section: Methodsmentioning
confidence: 99%
“…γ,δ-Unsaturated carboxylic acids bearing a tertiary alcohol at the α-position have been prepared by diastereodivergent Irelan-Claisen rearrangement studied by Zakarian and co-workers. 130 Starting from α-alkoxy-hydrocynnamic or lactic esters, and using KHMDS in toluene, the (Z)-enolate I was formed, which gave the syn-α,β-disubstituted hex-4-enoic acids (Scheme 85). On the other hand, using LDA the (E)-enolate II is formed, the chelation-controlled enolate generation being overcome, so providing anti-diastereomers.…”
Section: Scheme 80 Diastereodivergent Routes To Cis-(1r4s)-and Transmentioning
confidence: 99%